2017
DOI: 10.1016/j.aller.2016.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes among patients with asthma and parents and physicians towards influenza vaccination

Abstract: Asthmatic patients are not immunised regularly with influenza vaccine due to misperceptions about vaccine effectiveness and fear of adverse effects. Another important reason of this is that most the physicians caring for these patients neither immunise themselves nor recommend the vaccine to their patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 15 publications
2
4
0
4
Order By: Relevance
“…This study confirmed previous reports that the rates of pneumococcal and influenza vaccination are low in Turkey. 24,26,27 The findings of this study reflect real-life data and it allowed us to identify an area where efforts should be directed. As the main determinant for receiving one of the vaccines is the receipt of the other, it appears that awareness drives vaccination.…”
Section: Discussionmentioning
confidence: 57%
“…This study confirmed previous reports that the rates of pneumococcal and influenza vaccination are low in Turkey. 24,26,27 The findings of this study reflect real-life data and it allowed us to identify an area where efforts should be directed. As the main determinant for receiving one of the vaccines is the receipt of the other, it appears that awareness drives vaccination.…”
Section: Discussionmentioning
confidence: 57%
“…(12) H1N1 pandemisinin olduğu sezonda yaptıkları çalışmada grip aşısı yapılma oranını astımlı çocuklarda %16.8 olarak saptamıştır. Bir başka çalışmada da düzenli olarak her yıl grip aşısı yapılan astımlı çocukların oranı %12 olarak belirtilmiştir (13). Çalışmamızda 2016-2017 sezonunda astımlı çocuklarda grip aşısı yapılma oranı %25 olup bu oran yaş, cinsiyet, enfeksiyon sıklığı ve ev şartları bakımından benzer olan sağlıklı kontrollerden farklı değildi.…”
Section: Discussionunclassified
“…Bu oran ülkemizden yapılan bir başka çalışmaya göre oldukça yüksek gibi görünse de (13), çoğu çalışma sonucu ile benzerlik gösteriyordu (22). Bu oranın yüksek olması grip aşısı ile ilgili bilgi eksikliğinin yüksek olmasının yanında önyargının sanıldığı kadar yüksek olmadığını düşündürebilir.…”
Section: Discussionunclassified
See 2 more Smart Citations